Exploring the types of airway inflammation in hospitalized children with asthma - Peng Han; Ju Yin; Huimin Zou; Anxia Jiao; Yuliang Liu; Kunling Shen (BMC Pediatrics)
Abstract Background Asthma is a heterogeneous disease. Precise and personalized treatment is urgently needed to reduce the disease’s burden. Thus, exploring the different types of airway inflammation in hospitalized children with asthma is beneficial for accurately managing childhood asthma. Methods This retrospective study was conducted on children and adolescents with asthma who were hospitalized for asthma exacerbations. The classification cut-off values of blood eosinophil (EOS) were 150 (Standard 1), 300 (Standard 2), and 470/µL (Standard 3), respectively. Combined with specific IgE (sIgE, 0.7 kU/L), these individuals were divided into four airway inflammation types. We compared the proportion and characteristics of different airway inflammation. The P value < 0.05 indicated statistical significance. Results A total of 351 children were enrolled in our study. Based on standard 1, 39.3% of the subjects were classified as Only-atopy group, 11.7% displayed Only-EOS group, 29.6% exhibited Type 2 (T2)-high group, and 19.4% exhibited T2-low group. Under standard 2, 51.3% of the subjects were classified as the Only-atopy group, 5.4% displayed the Only-EOS group, 17.7% exhibited the T2-high group, and 25.6% exhibited the T2-low group. In standard 3, 57.8% of the subjects were classified as the Only-atopy group, 2.9% displayed the Only-EOS group, 11.1% exhibited the T2-high group, and 28.2% exhibited the T2-low group. Furthermore, our findings indicate that patients with T2 low airway inflammation have a longer time from onset to admission, a longer hospitalization time, a lower proportion of atopic dermatitis, and a higher proportion of siblings. Conclusion Regardless of the classification standard employed, the distribution of Only-atopy and Only-EOS was similar in different age periods. Moreover, the types of airway inflammation exhibited a consistent temporal pattern. The classification of airway inflammation in children based on peripheral blood and sIgE levels is a valuable tool for accurately treating asthma. Trial registration The study was registered at https://clinicaltrials.gov/ with the number: NCT05800379 on 05/04/2023.